SISTEM INFORMASI PENJUALAN BERBASIS WEB AKSESORIS MOBIL BERBASIS WEB PADA TOKO VARIASI JAYA MOBIL - Hadi Purwanto (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2020)
The social development of society in this world has progressed very rapidly. The most prominent thing in the development of information technology is the presence of new technology in the form of a computer network that is connected to the whole world, namely the internet. Jaya Mobil Variations Store is a store that is engaged in the sale of goods by offering various types of car accessories that can be used on all vehicles. The current sales system only serves direct sales, so it doesn't have an online sales system yet. The store only displays product catalogs to offer consumers and as a promotional medium. Customers placing orders or simply asking about prices must be via telephone, text message, or email which is then processed manually by employees or marketing of this company. Jaya Mobil Variation Stores have difficulty in managing sales transactions in large quantities manually. Developing business through the internet, expanding the market without having to incur high costs, selling products, and delivering information to customers, making it easier to serve consumers who need the product information they need